THE IMPACT OF CONTENT MARKETING, INFLUENCERS, AND E-PROMOTION ON PURCHASE INTENTION - Ida Ayu Iswari Pidada; Putu Gede Genta Taruna Suyasa (Jurnal Ekonomi dan Bisnis Airlangga, 2021)
Introduction: This study aims to analyze the impact of content marketing, influencers, and e-promotion on purchase intention.Methods: This research is conducted on the Instagram Social Media of Biang Denpasar Gallery with population of 1,040 customers and sample of 91 customers.Results: The results of the study show that content marketing, influencers, and electronic promotions have positive and significant impact on purchase intention. E-Promotion or online promotion as an activity through internet media.Conclusion and suggestion: The type of promotional media used will affect purchases at an online shop. E-Promotion has the highest and significant value. E-promotion can be improved by paying attention to the searchability indicator.